(untitled) (Tzintzun, Revista de Estudios Históricos, 2023)
The text reviews the use that has been made of the appraisals and taxes for the reconstruction of the great population aggregates of New Spain in the first century of Spanish domination, with a view to determining if it is really possible to continue accepting as valid the almost canonicals figures presented by Sherburne F. Cook and Woodrow W. Borah. Likewise, it is about understanding the nondemographic dynamics that influenced the configuration of the taxation of the tribute during the 16th century of New Spain.